A review of craniofacial disorders caused by spliceosomal defects. (1st May 2015) - Lehalle, D.; Wieczorek, D.; Zechi‐Ceide, R.M.; Passos‐Bueno, M.R.; Lyonnet, S.; Amiel, J.; Gordon, C.T.
<x xml:space="preserve">Abstract</x> The spliceosome is a large ribonucleoprotein complex that removes introns from pre‐mRNA transcripts. Mutations in EFTUD2, encoding a component of the major spliceosome, have recently been identified as the cause of mandibulofacial dysostosis, Guion‐Almeida type (MFDGA), characterized by mandibulofacial dysostosis, microcephaly, external ear malformations and intellectual disability. Mutations in several other genes involved in spliceosomal function or linked aspects of mRNA processing have also recently been identified in human disorders with specific craniofacial malformations: SF3B4 in Nager syndrome, an acrofacial dysostosis (AFD); SNRPB in cerebrocostomandibular syndrome, characterized by Robin sequence and rib defects; EIF4A3 in the AFD Richieri‐Costa–Pereira syndrome, characterized by Robin sequence, median mandibular cleft and limb defects; and TXNL4A in Burn‐McKeown syndrome, involving specific craniofacial dysmorphisms. Here, we review phenotypic and molecular aspects of these syndromes. Given the apparent sensitivity of craniofacial development to defects in mRNA processing, it is possible that mutations in other proteins involved in spliceosomal function will emerge in the future as causative for related human disorders.